The Distribution of Vasculokinase in Human Blood Vessels - Murray, Marvin; Johnson, Robert (Thrombosis and Haemostasis, 1962)
133 blood vessels were evaluated for vasculokinase concentration in the freshly morbid state. High concentrations of activity were found in the aorta, iliac artery, superior mesenteric artery and popliteal artery. Activity was occasionally found in the inferior vena cava and common iliacs veins. Other vessels evaluated had no activity. Evaluation of the data with respect to vas-culokinase activity and atherosclerosis suggests higher levels of vasculokinase in those vessels having atherosclerosis.